Party politics and prospects for democracy in North Africa - Storm, Lise (Studies on North Africa., 2014)
What are the prospects for democracy in North Africa in the wake of the Arab Spring? Addressing that question, Lise Storm provides a rich analysis of party politics in the region. Storm focuses on Tunisia, Morocco, and Algeria, examining the key characteristics and political dynamics of each country s party system as they have evolved over time. Her research sheds light not only on the origins, development, and functioning of these parties, but also on their contribution to the survival of authoritarianism, and their potential as vehicles for democratization.